Teaching Medical Students to Develop an ‘Appropriate’ Relationship with the Pharmaceutical Industry - Shankar, Ravi P (Nepal Journal of Epidemiology, 2014)
Considering the studies reported in the literature and trends in developed nations, teaching students about pharmaceutical promotion and how to deal with it should be an important part of the medical school curriculum. Appropriate interaction of doctors in the teaching hospital with MRs is essential as they serve as role models for students and as a strong influence on their future behavior. The hospital drug/medicine and therapeutics committee has an important role to play in this regard. The HAI-WHO manual on pharmaceutical promotion can be used as a guide for conducting sessions for students. Sensitizing students about pharmaceutical promotion and helping them develop an ‘appropriate’ relationship during their professional career is the need of the hour! DOI: http://dx.doi.org/10.3126/nje.v4i1.10124 Nepal Journal of Epidemiology 2014;4 (1): 299-300